2014
DOI: 10.3402/iee.v4.22251
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of hepatitis C virus among intravenous drug users in the Uppsala region of Sweden

Abstract: BackgroundEpidemiology and transmission patterns of hepatitis C virus (HCV) are important subjects as we enter a new era of treatment with directly acting antivirals (DAAs). The highest prevalence of HCV in developed countries is found among intravenous drug users (IDUs), where unsafe needle sharing practices provide the main route of infection. Efforts to prohibit the continuous spread of HCV among these groups have been initiated by the community services and health care providers. Our goal was to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Although the Core region is often used in phylogenetic analysis [ 28 – 30 ], this study found it was too conserved for clustering analysis. This study also found partial NS5B to be less informative than Core-E2 region, while other studies have used it for phylogenetic analyses [ 31 35 ] and suggest it is particularly suitable dating the introduction of an infection into a population using Bayesian methodologies [ 36 38 ].…”
Section: Discussionmentioning
confidence: 69%
“…Although the Core region is often used in phylogenetic analysis [ 28 – 30 ], this study found it was too conserved for clustering analysis. This study also found partial NS5B to be less informative than Core-E2 region, while other studies have used it for phylogenetic analyses [ 31 35 ] and suggest it is particularly suitable dating the introduction of an infection into a population using Bayesian methodologies [ 36 38 ].…”
Section: Discussionmentioning
confidence: 69%
“…(25,26) The sharing of equipment for intravenous use of drugs may lead to transmission of HCV virus. (27) The majority of HCV-Ab negative HCWs washed their hands after exposure to blood or body fluid. This was comparable to the results of Munier et al, (14) who declared that hand hygiene is a cost-effective intervention to prevent heath care settings infections.…”
Section: Discussionmentioning
confidence: 99%